2021
DOI: 10.1177/23337214211047642
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Anxiety, Stress, and Concern of COVID-19 Infection in Older Adults During the First and the Second Waves of the COVID-19 Pandemic in Slovakia

Abstract: Objectives: This cross-sectional online study examined the role of socio-demographic and psychological characteristics in predicting anxiety, stress, and concern of coronavirus (COVID-19) infection in older adults during the first and second waves of the COVID-19 pandemic in Slovakia. Methods: Six hundred and seven older adults (Sample 1) and 156 older adults (Sample 2) participated in the study during the first and second waves of the COVID-19 pandemic, respectively. The older adults completed a battery of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 55 publications
(102 reference statements)
0
11
0
3
Order By: Relevance
“…Although there has been literature on the powerlessness experienced by residents in COVID-19 pandemic (25)(26)(27), few studies have focused on this symptom of anti-COVID-19 medical staff. Our study found that powerlessness is also a symptom frequently reported by anti-COVID-19 medical staff when seeking psychological assistance services.…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been literature on the powerlessness experienced by residents in COVID-19 pandemic (25)(26)(27), few studies have focused on this symptom of anti-COVID-19 medical staff. Our study found that powerlessness is also a symptom frequently reported by anti-COVID-19 medical staff when seeking psychological assistance services.…”
Section: Discussionmentioning
confidence: 99%
“…Es lässt sich vermuten, dass Veränderungen wie diese zu einer Zunahme von Ängsten und Einsamkeit bei älteren Menschen führen. Verschiedene Studien belegen eine enge Verbindung zwischen Einsamkeit und Isolation sowie dem Erleben von Unsicherheit mit psychischen Erkrankungen, auch im Rahmen der Pandemie [ 6 , 7 ]. Dagegen sprechen andere Studien eher dafür, dass ältere Menschen mit einer gewissen Gelassenheit durch die Zeit der Krise kommen [ 2 , 3 , 14 ].…”
Section: Hintergrund Und Ziel Der Arbeitunclassified
“…Dagegen sprechen andere Studien eher dafür, dass ältere Menschen mit einer gewissen Gelassenheit durch die Zeit der Krise kommen [ 2 , 3 , 14 ]. Hier ist anzunehmen, dass u. a. das Erleben von Selbstwirksamkeit eine mögliche Gelassenheit in der Krise moderiert [ 7 ]. Dabei wird Selbstwirksamkeit als Vertrauen in die eigenen Kompetenzen verstanden, als Überzeugung, schwierige Situationen erfolgreich bewältigen zu können [ 1 ].…”
Section: Hintergrund Und Ziel Der Arbeitunclassified
See 1 more Smart Citation
“…Moreover, pandemics that involve highly infectious diseases like COVID-19 usually result in mental health challenges, such as fear and anxiety (Lee, 2020;Wango, Wairire, & Kimamo, 2020), and may interfere with the behaviour and overall well-being of the populace (Camero, 2020;Lee, 2020). Hence, peoples' ability to cope with threatening events, in this case, the COVID-19 pandemic, remains topical (Koverova, Raczova´, & Holevova, 2021). In that regard, the question remains on the identification of the individuals that feel vulnerable and anxious about the pandemic and the correlates of the concomitant anxiety.…”
Section: Introductionmentioning
confidence: 99%